2017
DOI: 10.1109/jbhi.2017.2677901
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between Gait on Stairs and Flat Surfaces in Relation to Fall Risk and Future Falls

Abstract: We used body-worn inertial sensors to quantify differences in semi-free-living gait between stairs and on normal flat ground in older adults, and investigated the utility of assessing gait on these terrains for predicting the occurrence of multiple falls. Eighty-two community-dwelling older adults wore two inertial sensors, on the lower back and the right ankle, during several bouts of walking on flat surfaces and up and down stairs, in between rests and activities of daily living. Derived from the vertical ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 44 publications
0
39
0
Order By: Relevance
“…The use of inertial sensors can be used to tackle the identified shortcomings of the optoelectronic motion capture system [15], as many studies have demonstrated their validity in the estimation and assessment of gait features [3]. However, these sensors also need to be mounted on distinct and specific locations of the users" body when one wishes to monitor their gait.…”
Section: B Motivation and Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of inertial sensors can be used to tackle the identified shortcomings of the optoelectronic motion capture system [15], as many studies have demonstrated their validity in the estimation and assessment of gait features [3]. However, these sensors also need to be mounted on distinct and specific locations of the users" body when one wishes to monitor their gait.…”
Section: B Motivation and Contributionmentioning
confidence: 99%
“…Clinical gait analysis using temporal gait features, such as those mentioned above, has gained popularity for instance for the evaluation of rehabilitation progression in patients after a surgical procedure (e.g., after a knee replacement) [2], or in the prediction of fall risks in the elderly population [3]. However, the acquisition and evaluation of the features from which BGIs are derived is usually performed in dedicated laboratories, often resulting in an expensive and a timeconsuming task.…”
Section: Accepted Manuscript I Introductionmentioning
confidence: 99%
“…Specifically, fall prediction can be verified by analyzing fall risk assessments of the elderly, considering combinations of risk factors, and data produced by wearable sensors [41]. Body-worn inertial sensors can be used to explore the differences in semi-free-living gait between activity on stairs and on a regular, flat floor surface in regard to elderly and impaired daily activities [42]. A single standing time model was also used for predicting the fall risk of the elderly population [43].…”
Section: Introductionmentioning
confidence: 99%
“…The gold standard for mobility and gait monitoring most often includes full-body motion capture systems, video systems, and force places that are capable of providing highly detailed and quantitative gait data [6,7]. These systems, however, are often prohibitively expensive for most clinical settings, require the need for additional skilled technicians, and are limited to indoor use in laboratory settings [8][9][10]. Moreover, these solutions can only provide gait data for a limited number of strides thus preventing them from being a viable option for community-based, long-term monitoring.…”
Section: Introductionmentioning
confidence: 99%